Voltage stability assessment using TCSC and SVC based FACTS controllers - Jena, Ramakanta; Swain, Sarat Chandra; Chirantan, Shaswat; Dash, Ritesh; Panda, P.C (International Journal of Advances in Applied Sciences, 2021)
The Most causes of Voltage instability is the sources of reactive power .In order to protect the total system from voltage instability the reactive  loads can be reduced or extra reactive power can be added to reach the Voltage collapse point .The Flexible AC transmission devices(FACTS) have made it flexible and possible to prevent  Voltage instability by  Fast and Flexible control method .  Voltage collapse point is predicted with  TCSC and  SVC  devices and is compared with each other. The Voltage stability Indicator is derived to identify the voltage collapse point. it is concluded that voltage stability index provides a simple means to predict vulnerability of a bus in a Multibus system for voltage collapse.